Transgenic Mice with Chronic NGF Deprivation and Alzheimer's Disease-Like Pathology Display Hippocampal Region-Specific Impairments in Short- and Long-Term Plasticities - Houeland, Gry; Romani, Armando; Marchetti, Cristina; Amato, Gianluca; Capsoni, Simona; Cattaneo, Antonino; Marie, Hélène (The Journal of neuroscience, 2010)
The etiology of Alzheimer's disease (AD) remains elusive. The “amyloid” hypothesis states that toxic action of accumulated β-amyloid peptide (Aβ) on synaptic function causes AD cognitive decline. This hypothesis is supported by analysis of familial AD (FAD)-based transgenic mouse models, where altered amyloid precursor protein (APP) processing leads to Aβ accumulation correlating with hippocampal-dependent memory deficits. Some studies report prominent dentate gyrus (DG) glutamatergic plasticity alterations in these mice, while CA1 plasticity remains relatively unaffected. The “neurotrophic unbalance” hypothesis, on the other hand, states that AD-related loss of cholinergic signaling and altered APP processing are due to alterations in nerve growth factor (NGF) trophic support. This hypothesis is supported by analysis of the AD11 mouse, which exhibits chronic NGF deprivation during adulthood and displays AD-like pathology, including Aβ accumulation and hippocampal-dependent memory deficits. In this study, we analyzed CA1 and DG glutamatergic plasticity in AD11 mice to evaluate whether these mice also share with FAD models a common phenotype in hippocampal synaptic dysfunction. We report that AD11 mice display age-dependent short- and long-term DG plasticity deficits, while CA1 plasticity remains relatively spared. We also report that both structures exhibit enhanced glutamatergic transmission under lower, yet physiological, neurotransmitter release conditions, a defect that should be considered when further evaluating hippocampal synaptic deficits underlying AD pathology. We conclude that severe deficits in DG plasticity represent another common denominator between these two etiologically different types of AD mouse models, independent of the initial insult (overexpression of FAD mutation or NGF deprivation).